O wybranych aspektach determinujących nauczanie i uczenie się języka rosyjskiego (drugiego obcego) - wnioski z badań - Karolczuk, Marzanna (Neofilolog, 2010)
The aim of the present paper is to attempt to analyze selected factors which influence the learning of a second or foreign language. The goal is also to present the results of preliminary studies based on the observations of Russian language lessons. The introduction of a second foreign language into schools makes teaching multilingual. Students’ native language together with the languages they learn in and outside educational institutions all contribute to establishing a unique linguistic and cultural environment. The process of teaching and learning of a second language should refer to students’ knowledge and skills, which they acquired during their previous learning experiences.